Carcinoma Urotelial em cadela - Relato de caso - Alcântara, José Gabriel Gonçalves (Universidade Federal do Tocantins, 2023)
Transitional cell carcinoma (CTC) is the most common bladder tumor in dogs. It has multifactorial etiology and its symptoms are often confused with those of urinary tract infection (hematuria, dysuria, polaciuria). Although CTC may be suspected based on clinical signs, imaging methods (ultrasonography) or urinary cytology, the diagnosis may be confirmed by histopathological examinations. Unfortunately, it is considered a tumor of bad prognosis and possibly incurable, so there is great interest in researching new methods of prevention, other means of early diagnosis and new modalities of treatment. This study aims at an up-to-date bibliographic review of the topics addressed, together with a description of the activities carried out during the supervised course stage, the site of the internship and the clinical case of CTC in dogs.